Effectiveness of Online Learning in Technical And Vocational Education and Training (TVET): A Meta-Analysis Study from a Malaysian Perspective - Sukri Saud, Muhammad; Faiz Bin Mohamad Noor, Mohamad; Kamin, Yusri; Zolkifli Abd. Hamid, Mohd; Hizwan Mohd Hisham, Mohd (KnE Social Sciences, 2022)
Learning and teaching have been affected by the COVID-19 pandemic.However, besides its catastrophic impact, it is seen as a catalyst for the implementation of online learning. Online learning has become the main means to implement learning and teaching processes during the pandemic. This study was conducted to identify the effectiveness of online learning in Technical and Vocational Education and Training (TVET). The study uses a meta-analytical approach in which a total of 10 articles have been identified using ’Google’ and ’Google Scholar’ engine searches and were then finely reviewed. Among factors which contribute towards the effectiveness of online learning are the technique and delivery of instructors, interactive learning, learning syllabus, readiness and motivation of students. Keywords: Interactive Learning, Online Learning, Motivation